Pendekatan Holistik Guru PAI dalam Meningkatkan Kecerdasan Religius dan Keterampilan Sosial dan Menekan Perilaku Bullying Anak Sekolah Dasar - Zain, Sri Kurnia; Andri, Sri; Mujib, Abdul (UIN Sunan Gunung Djati Bandung, 2025)
This study examines the role of Islamic Education (PAI) teachers in enhancing religious intelligence, reducing bullying behavior, and improving social skills among elementary school students through a holistic approach. This approach integrates religious, moral, and social values into the learning process. The research employs a quantitative method with a descriptive correlational design involving 150 randomly selected students. The findings indicate that PAI teachers play a significant role in fostering religious intelligence, decreasing bullying behavior, and enhancing social skills. Teachers who integrate religious values into their teaching help shape students' religious character, strengthen moral awareness, and improve their ability to engage positively with their social environment. The holistic approach, which involves collaboration among teachers, students, and the school community, has proven effective in creating an environment that promotes religious values, social harmony, and a reduction in bullying incidents. The study recommends that PAI teachers continue to develop holistic teaching methods to cultivate a school culture that is religious, harmonious, and supportive of students' social skill development.